Response surface methodology for studying the effect of processing conditions on some nutritional and textural properties of bambara groundnuts (Voandzei subterranea) during canning - Ohene Afoakwa, E.; Budu, A.S.; Bullock Merson, A. (My University, 2007)
Response surface methodology and central composite rotatable design for K=3 was used to study the combined effect of blanching, soaking and sodium hexametaphosphate salt concentration on moisture, ash, leached solids, phytates, tannins and hardness of bambara groundnut during canning. Regression models were developed to predict the effects of the processing parameters on the studied indices. Significant interactions were observed between all the factors with high regression coefficients (64.4_82.6%). Blanching and soaking of the seeds prior to canning led to increases in moisture content and leached solids, while significant decreases were observed for phytates, tannins and hardness of the canned bambara groundnuts. Increasing the concentration of sodium salt added during soaking caused significant (P5/0.05) decreases in phytates, tannins and the hardness of the seeds, suggesting that pre-canning treatments of blanching, soaking and sodium hexametaphosphate salt addition can be used to effectively reduce the phytates, tannin levels with minimal mineral (ash) loss and enhanced textural integrity of the canned bambara groundnuts.
Keywords: soaking; blanching; sodium hexametaphosphate salt; Response surface methodology; anti-nutritional factors; textural properties